Competency of Tax Employee Communication on Tax Paying Behavior in Taxpayer in Medan City - Situmorang, Doris Corazon; Asmara, Sakhyan; Zulkarnain, Iskandar (Budapest International Research and Critics University, 2021)
The purpose of this study was to analyze the effect of tax employee communication competence on tax paying behavior and analyze the magnitude of the correlation between taxpayer characteristics in influencing tax employee communication competence on tax paying behavior among taxpayers Medan city tax. The theory used is the theory of communication competence, theory of competence and theory of behavior. The researcher used a quantitative approach with the correlational method. The population is all individual taxpayers who are active and registered until the end of 2019 in the city of Medan. The research sample was 100 respondents using purposive proportional random sampling technique. Data collection techniques were carried out through questionnaires. The results of the study indicate that there is an influence of communication competence on the behavior of paying taxes among taxpayers in the city of Medan. This is evidenced by the value of t arithmetic > t table which is 9.612 > 1.984 at a significance level of 0.05. Then the characteristics of taxpayers seen from education, age, and occupation do not affect the communication competence of tax employees on tax-paying behavior. This is because the path coefficient value has a very small value <0.05. Meanwhile, the characteristics of taxpayers based on gender also influence the communication competence of tax employees on tax-paying behavior, which shows that women tend to be more obedient than men in terms of tax-paying behavior.